ANALISIS PROBABILITAS KENDARAAN RODA DUA MENYEBERANGI SUNGAI KAPUAS MENGGUNAKAN JEMBATAN KAPUAS 2 DAN KAPAL - Nasution, Barry Muhammad; Akhmadali, -; AS, Syafaruddin (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Transportation that can be used by two-wheeler riders to cross Kapuas River in Sungai Raya consists of two options, there are Kapuas Bridge 2 and klotok in Sungai Ambangah - Arang Limbung village. The subjects of this study are two-wheeler riders that came from Kapur, Mekar Baru, Madu Sari and Sungai Ambangah village with destination to Sungai Raya, Teluk Kapuas and Arang Limbung village. The purpose of this study was to examine the factors that can be affected the two-wheeler riders in choosing a mode of transport crossing (mileage, travel time, value of time, and expense) on both routes that were observed and also obtain a mode choice models by using logit models. The relationship between these factors are described by a mathematical model. This model is used to determine the sensitivity model from responses of two-wheeler riders who choose klotok, if there’s a change in one of factor that influence the mode choice.The data collection process lasted for 4 days at two different locations, there are Desa Kapur with the direction toward Kapuas Bridge 2 and in boat dock. The information that have to require are origin-destination survey, speed surveys, and two-wheeler’s income that came from Kapur, Mekar Baru, Madu Sari and Sungai Ambangah village.The analysis showed that there is significant relationship between distance, travel time, value of time and expense that affect two-wheeler riders from Kapur, Mekar Baru, Madu Sari and Sungai Ambangah village to use klotok. Keywords: mode choice, sensitivity, logit model, two-wheeler riders